KARAKTERISTIK PRIBADI DALAM PERKEMBANGAN HUMANRELATIONS - Cindy Fatika Sari (Journal of Dialogos, 2024)
This article describes a healthy personality and its characteristics, as well as human relations activities and applications in practice. This research uses a qualitative approach. The purpose of making this article is to know about personal with good human relations, know about the application of human relations in practice and know the characteristics of a healthy personality. The results of the research show that there are three models of motivational communication in personal good human relations, namely the traditional model, the human relations model, and the resource model.